2018
DOI: 10.1016/j.solmat.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Sandstorm erosion testing of anti-reflective glass coatings for solar energy applications

Abstract: Components for concentrating solar power applications can suffer from optical performance loss due to their permanent exposure to the environment. There is still lack of experience regarding the destructive effects of sand-and duststorms on glass envelope materials for receiver tubes of parabolic-trough collectors for concentrating solar power (CSP) plants. So far no accelerated aging guideline is formulated yet to account for the performance loss of optical components due to particle erosion to a realistic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 16 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…This strongly suggests that the AS treatment not only avoid the adherence of sand particles but also increases the abrasion resistance of the surface. Similar results were obtained previously in samples tested in a sandstorm chamber, where the use of the AS treatment reduced considerably the erosion rate (Wiesinger et al, 2018).…”
Section: Effect Of Sand and As Treatmentsupporting
confidence: 90%
See 1 more Smart Citation
“…This strongly suggests that the AS treatment not only avoid the adherence of sand particles but also increases the abrasion resistance of the surface. Similar results were obtained previously in samples tested in a sandstorm chamber, where the use of the AS treatment reduced considerably the erosion rate (Wiesinger et al, 2018).…”
Section: Effect Of Sand and As Treatmentsupporting
confidence: 90%
“…Concerning the effect of climatic conditions, it has been found that high precipitation accompanied by high wind velocity create a natural cleaning, but the combination of dust with low precipitation or high humidity produces mud patches that cause an opposite effect and may result in permanent decrease in solar efficiency (Mazumder et al, 2015). Recently, the application of AS treatments on the AR coated glass is generating great interest as the transmittance by soiling is reduced as well as the abrasion produced by sand particles and/or cleaning processes is also diminished (San Vicente et al, 2011;Pendse et al, 2018;Quan and Zhang, 2018;Wiesinger et al, 2018). Additionally, cleaning processes of optical surfaces in solar power plants is a key point as they can degrade the optical surface and as these processes imply important operation and maintenance (O&M) costs in manpower.…”
Section: Introductionmentioning
confidence: 99%
“…Wiesinger et al [169] tested different anti-reflective coatings as an erosion mitigation; the coatings improved the optical performance of the tested glass by around 4.9%; however, if the CSP site often suffers extreme weather conditions, anti-reflective coatings would cause faster optical losses. Even though adding a hydrophobic coating to an anti-reflective one slightly reduced optical performance, it was very effective against sand erosion.…”
Section: Anti-soiling Coatingsmentioning
confidence: 99%
“…A comparative study among different anti-reflective coatings after a laboratory erosion treatment is dealing with this issue [24] in more detail.…”
Section: Defects On Brittle Materialsmentioning
confidence: 99%